Efforts to Improve the Physical Fitness of MI Students Through Traditional Games Fort - Rizki, A'an Taufik; La Kamadi; Sofyan Haeruddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
This research aims to: (1) describe the application of the traditional game of Bentengan in physical education learning for class V students of MI Ngingas Salamrejo, Trenggalek Regency; and (2) describe the application of the traditional game of Bentengan to improve the fitness of class V students of MI Ngingas Salamrejo, Trenggalek Regency. This type of research uses a Classroom Action Research design. This research was conducted in two cycles, with each cycle consisting of one meeting. Meanwhile, data collection techniques use observation, field notes, documentation, and tests. The results of the research show that the application of the traditional game Bentengan in physical education class V learning at MI Ngingas Salamrejo, Trenggalek Regency, can be well implemented. This proves that in each cycle, the indicators can be achieved well according to the RPP created, namely the average score obtained at 79% in cycle I and increasing to 83% in cycle II. When applying the traditional game of fortification, the average score obtained in cycle I was 98% and increased to 100% in cycle II. Implementing the traditional game of fortification can improve students' fitness. This is also evident from the average student fitness of 86% in cycle I and increasing to 90% in cycle II.